Traffic Congestion and Traffic Safety in the 21st Century : challenges, innovations, and opportunities, Chicago Illinois, June 8-11, 1997 : proceedings of the conference sponsored by Urban Transportation Division, ASCE, Highway Division, ASCE - Benekohal, R. F.; American Society of Civil Engineers. Urban Transportation Division; American Society of Civil Engineers. Highway Division (New York, N.Y. : American Society of Civil Engineers)
Includes bibliographical references and indexes